Health related quality of life among Saudi children and adolescents with celiac disease - Al Nofaie, Norah D. (Saudi J Gastroenterol, 2019)
BACKGROUND/AIMS: Celiac disease (CD) is an immune-mediated enteropathy triggered by gluten ingestion in genetically susceptible individuals. This study reports on the quality of life (QOL) of Saudi children and adolescents with CD. PATIENTS AND METHODS: This is a case control study that included Saudi patients with CD, aged 9-18 years, who attended CD Clinic at KAU between February 2017 and July 2018. The study was conducted using the Short-Form (SF-36) questionnaire for all candidates, CD-specific QOL questionnaire for the CD patients group, and CD screen questionnaire for the control group. RESULTS: Overall, 354 subjects were studied (111 CD patients and 243 control). Female subjects constituted 56.8% of both patient and control groups. In the generic SF-36 questionnaire, QOL was comparable between patients and controls in all domains except for the general health domain, which showed difference in favor of the controls (55.01 ± 26.41 and 62.96 ± 18.16, P = 0.005). We also found that males have lower QOL scores in the domains comprising health change (P = 0.02), physical functioning (P = 0.04, role functioning/emotional and emotional well-being (P = 0.049). The CD-specific QOL showed excellent and good scores for 79.3% of patients overall in the tested domains. Patients with poor adherence showed poor QOL in all generic (SF-36) domains but not in CD-specific domains. CONCLUSION: The HRQOL for Saudi CD children on GFD is generally comparable to the healthy control with exception of the general health domain. Adherence to the GFD improves the generic (SF-36) QOL domains.